MONKEY POX: A NEW CONCERN (Journal of Pharmaceutical Negative Results, 2022)
Monkey pox is an infectious viral disease which spread from animals to humans. This virus is a new concern, as recently the identification of emerging cases of monkey pox virus other than African Continent in May 2022.It showed its spread in other parts of world because of international tourism and exchange of certain animals . Hence it is important to evaluate and discuss the management of monkeypox infections in humans to prevent the spread of the disease. The objective of this review is discuss the spread of monkey pox disease world-wide, study its symptoms for prompt identification of the disease with the aim to abolish all possible modes of transmission to protect public health and to prevent the possibility of spread of another pandemic, after COVID-19.